INTEGRASI ETNOSAINS TRI TANGTU KAMPUNG NAGA DALAM PENGEMBANGAN E-MODUL INTERAKTIF MATERI EKOSISTEM SEKOLAH DASAR - Sunardi, Dehani Airin; Ghullam Hamdu; Muhammad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the limited availability of contextual and culturally relevant learning resources in elementary science education, particularly for teaching ecosystem concepts that are often perceived as abstract by students. The lack of integration between scientific concepts, local wisdom, and interactive digital media has contributed to passive learning practices and low conceptual understanding. This research aims to develop an interactive e-module based on ethnoscience by integrating the local wisdom of Tri Tangtu Kampung Naga as a learning resource for ecosystem topics in elementary schools. The study employed a Design-Based Research (DBR) methodology, which involved iterative stages of problem analysis, design and development of the e-module, implementation in real classroom settings, evaluation, and refinement. The research was conducted with fifth-grade elementary school students and involved expert validation as well as user practicality testing by teachers and students. The results indicate that the developed ethnoscience-based interactive e-module is valid, practical, and suitable for use as a learning resource. The integration of Tri Tangtu Kampung Naga successfully contextualized ecosystem concepts, enhanced student engagement, and supported meaningful learning experiences. These findings suggest that interactive e-modules integrating local wisdom can serve as effective instructional media to improve conceptual understanding while fostering environmental awareness and cultural appreciation among elementary school students.